On Multiplicative Topological Invariants of Magnesium Iodide Structure - Zhiqiang Zhang; Haidar Ali; Asim Naseem; Usman Babar; Xiujun Zhang; Parvez Ali (Journal of Mathematics)
In recent times, the applications of graph theory in molecular and chemical structure research have far exceeded human expectations and have grown exponentially. In this paper, we have determined the multiplicative Zagreb indices, multiplicative hyper-Zagreb indices, multiplicative universal Zagreb indices, sum and product connectivity of multiplicative indices, multiplicative atom-bond connectivity index, and multiplicative geometric-arithmetic index of a famous crystalline structure, magnesium iodide MgI2.